O professor da Educação Especial e o processo de ensino-aprendizagem de alunos com autismo - Santos, Andréa Rizzo dos [UNESP]; Lourenço, ana Carla; Capellini, Vera Lucia Messias Fialho [UNESP] (Universidade Federal de Santa Maria, 2013)
This paper has as subject autism, and sought to verify how the process of teaching and learning of students with autism occurs in a special education school. The Infantile Autism is today sorted as one of the “Global Developmental Disorders (PDD)” and is characterized by a severe and global impairment in several areas of development, such as reciprocal social interaction skills, communication skills and presence of stereotypic behavior, interests and activities. This study aimed to identify the teaching methodology used with adolescents with autism in special education and see in what ways this methodology assists in the teaching and learning of these students. To this end, participated in this study a teacher, expert in this issue, and three students with autism in a Special Education School located within the State of São Paulo. For data collection, 19 observations of activities performed by students with autism in the classroom were conducted and a semi-structured interview with the specialized teacher was applied. The results revealed that the teacher mentioned above does not use any specific teaching methodology to assist in the teaching and learning of these students, although there are some specific methodologies for individuals with autism, which are used in special education schools. Thus, there is a gap in the teaching process on the part of the teacher and an uncertainty about the learning process of these students with autism in this institution.

O presente trabalho tem como tema o autismo, e buscou verificar como ocorre o processo de ensino-aprendizagem de alunos com autismo em uma escola de educação especial. O Autismo infantil é hoje classificado como um dos “Transtornos Globais do Desenvolvimento (TGD)” e é caracterizado por um comprometimento grave e global em diversas áreas do desenvolvimento, como nas habilidades de interação social recíproca, habilidades de comunicação e presença de estereotipias de comportamento, interesses e atividades. Esse trabalho teve como objetivo identificar a metodologia de ensino utilizada com adolescentes com autismo na educação especial e verificar em que aspectos essa metodologia auxilia no processo de ensino-aprendizagem desses alunos. Para tal, participaram da pesquisa uma professora especialista e três alunos com autismo de uma Escola de Educação Especial localizada no interior do Estado de São Paulo. Para a coleta de dados foram realizadas 19 observações de atividades realizadas pelos alunos com autismo em sala de aula e aplicada uma entrevista semi-estruturada à professora especialista. Os resultados demonstraram que a professora especialista não utiliza nenhuma metodologia de ensino específica para auxiliar no processo de ensinoaprendizagem desses alunos, apesar de existirem algumas metodologias específicas para pessoas com autismo, que são empregadas em escolas de educação especial. Assim, verifica-se uma lacuna no processo de ensino por parte da professora e uma incerteza quanto ao processo de aprendizagem desses alunos com autismo, nessa instituição.
Teacher of Special Education and teaching-learning process of students with autism
Keywords: autismo; Educação Especial; Formação de professores